Mycosynthesis and characterization of selenium nanoparticles using standard penicillium chrysogenum PTCC 5031 and their antibacterial activity: A novel approach in microbial nanotechnology - Hossein Vahidi (Nanomedicine Journal, 2020)
Objective(s): This study deals with mycosynthesis and characterization of selenium nanoparticles (SeNPs) using the Penicillium chrysogenum PTCC 5031 and evaluating their antibacterial activity. Materials and Methods: The formation of SeNPs was confirmed with the color change from pale yellow to orange. Tyndall effect also confirmed the formation of colloidal systems through the samples. The SeNPs were characterized using different analytical techniques including photon correlation spectroscopy (PCS), Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM), Energy Dispersive X-ray (EDX), X-ray diffraction (XRD) and Fourier Transform Infrared (FT-IR) analysis. Results: Our findings revealed that SeNPs were fairly uniformed with good monodispersity and the lesser aggregation of particles in pH value of 7 with the average hydrodynamic size of 24.65 nm, polydispersity index (PdI) of 0.392 and zeta potential of -34 mV. The SeNPs revealed antibacterial activity against gram positive bacteria including Staphylococcus aureus, and Listeria monocytogenes with the zone of inhibition (ZOI) of 10 and 13 mm, respectively. Conclusion: The results of this study provided a potential solution to the growing need for the development of cost-effective and eco-friendly ways of nanoparticle synthesis to overcome the microbial resistance and control the infectious diseases. However, further investigations are required to demonstrate the efficacy of SeNPs through in vivo models.